A new troglobitic species of Metopioxys (Staphylinidae: Pselaphinae) from Brazilian iron ore caves - Asenjo, Angélico; Pietrobon, Thadeu; Ferreira, Rodrigo Lopes (Zootaxa, 2019)
A new species, Metopioxys carajas, is described from caves of Pará state in Brazil. Photographs and the major diagnostic characters are provided for the new species.